2013
DOI: 10.1002/jrs.4276
|View full text |Cite
|
Sign up to set email alerts
|

Micro‐Raman investigations of early stage silver corrosion products occurring in sulfur containing atmospheres

Abstract: Silver is a soft, lustrous metal with the highest electrical and thermal conductivity. Due to these properties, it has many applications as a precious material both in pure and alloy form (ornaments, jewellery, utensils, coins), but also in several technological fields, considering silver compounds (e.g. photography, electric and electronic industry). As a consequence of this, silver and its by‐products are regularly exposed to different atmospheres where a wide spectrum of agents (e.g. moisture, temperature, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
83
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 90 publications
(87 citation statements)
references
References 20 publications
3
83
0
1
Order By: Relevance
“…a) Ag 3d and b) S 2p for pure silver; c) Ag 3d, d) S 2p, e) Cu 2p and f) Cu Auger LMM for sterling silver. [43,44]. The presence of this compound testifies the high tendency of silver to oxidation under ambient conditions.…”
Section: Micro-raman Spectroscopymentioning
confidence: 93%
See 2 more Smart Citations
“…a) Ag 3d and b) S 2p for pure silver; c) Ag 3d, d) S 2p, e) Cu 2p and f) Cu Auger LMM for sterling silver. [43,44]. The presence of this compound testifies the high tendency of silver to oxidation under ambient conditions.…”
Section: Micro-raman Spectroscopymentioning
confidence: 93%
“…7c) results in the appearance of a couple of bands at 185 and 237 cm −1 that are assigned to the Ag-S stretching and bending vibrations modes of Ag 2 S, respectively [43,44]. At 1064 nm, the Raman spectra reveal slight differences in the intensity of the Ag 2 S bands.…”
Section: Micro-raman Spectroscopymentioning
confidence: 99%
See 1 more Smart Citation
“…However, silver sulfide (Ag 2 S) and silver sulfate (Ag 2 SO 4 ) are common atmospheric silver corrosion products that form on the probe surface. Their Raman bands, which appear around 188, 243, and 273 cm -1 for Ag 2 S and 432, 460, 595, 623, 970 (strong), and 1079 cm -1 for Ag 2 SO 4 [2], can coincide with spectral regions of interest such as the radial breathing mode of carbon nanotubes (CNT) [3]. It was also shown that the electric field enhancement decreases with the aging of the silver surface [4]; the thickness of Ag 2 S increases over time as it is not a self-limiting process confined to the surface [5].…”
Section: Introductionmentioning
confidence: 99%
“…carried out a micro‐Raman investigation of early‐stage silver corrosion products occurring in sulfur containing atmospheres. The experiments highlight micro‐Raman spectroscopy as a highly surface‐sensitive technique enabling the detection of both adsorbed chemical species and crystalline corrosion products of only several monolayers of thickness . Sanson and coworkers studied carrier concentration profiles in Al‐implanted Ge by micro‐Raman spectroscopy using different excitation wavelengths.…”
Section: Introductionmentioning
confidence: 99%